2019
DOI: 10.18004/rspp.2019.diciembre.29-34
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV/Syphilis and risk behaviors in female sex workers in Paraguay

Abstract: Prevalencia del VIH/Sífilis y comportamientos de riesgo en mujeres trabajadoras sexuales en Paraguay RESUMEN Introducción: En Paraguay, la epidemia del VIH se encuentra concentrada en población clave. La ruta principal de transmisión de las infecciones de transmisión del VIH y la Sífilis es la sexual. Las mujeres trabajadoras sexuales (MTS) presentan riesgo incrementado debido a su trabajo sexual y sus comportamientos de riesgo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Other researchers have shown that early age at the beginning of sexual activity and work significantly increases the risk of STD. [27] We observed that the number of clients served per day does not behave as a risk factor associated with syphilis; in fact, the highest prevalence was found in those who had fewer clients per…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Other researchers have shown that early age at the beginning of sexual activity and work significantly increases the risk of STD. [27] We observed that the number of clients served per day does not behave as a risk factor associated with syphilis; in fact, the highest prevalence was found in those who had fewer clients per…”
Section: Discussionmentioning
confidence: 69%
“…[26] For example, a study obtained a prevalence of syphilis of 8.59% (95% CI 5.78-12.59), identifying as risk factors the low percentage of condom use with a stable partner, high drug consumption, and low-risk perception. [27] Although educational level is not an independent risk factor for syphilis infection, the level of education is one of the most essential variables in measuring socioeconomic status and its effects on the health status of a population. It has been observed that FSWs in brothels have a better level of knowledge about STIs, reducing risk behaviors and impacting the prevalence of syphilis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations